An Investigation on Acoustic Wave Focalization by a Square Lattice Flat Lens - Serkan ALAGOZ (Archives of Acoustics)
A sonic crystal consists of a finite-size periodic array of scatters embedded in a background material. One of the fascinating properties of sonic crystals is the focusing phenomenon. In this study, the near field focusing effect of a solid-air 2D sonic crystal lens with a square lattice configuration is investigated in the second frequency band. The band structure and equifrequency contour of the crystal are analyzed to reveal the dispersion of an acoustic wave on the crystal structure. The frequency dependence of the acoustic wave focalization by the sonic crystal flat lens is demonstrated via Finite Difference Time Domain simulation results and experimental measurements.